Exact and numerical traveling wave solutions for nonlinear coupled equations using symbolic computation - Kaya, D; Inan, IE (Elsevier Science Inc, 2004)
We find the explicit and numerical traveling wave solutions for a coupled KdV equation and a coupled MKdV equation by using the decomposition method with help of symbolic computation. By using this method, the solutions were calculated in the form of a convergent power series with easily computable components. The convergence of the method as applied to the coupled KdV and MKdV equations is illustrated numerically. (C) 2003 Elsevier Inc. All rights reserved.
Keywords: the Adomian decomposition method; a coupled KdV equation; a coupled MKdV equation; traveling wave solution; symbolic comptuation